2010
DOI: 10.3109/09273972.2010.525778
|View full text |Cite
|
Sign up to set email alerts
|

Large-Angle Strabismus: Can a Single Surgical Procedure Achieve a Successful Outcome?

Abstract: A good surgical outcome can be obtained in large-angle strabismus with a single surgical procedure, though a randomized controlled study needs to be done to establish whether three-muscle surgeries give better results than two-muscle surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In our study, we conclude that the prevalence of secondary surgery in squinted eye patients was low, but With regard to the results of treating amblyopia by occlusion , there were a high number in delaying treating amblyopia which may suggest the distance of the patients' domicile from hospital or lack of education , So we recommend the importance of inform and educate other health care practitioners, including primary care physicians, as well as teachers, parents, and patients about the visual complications of strabismus and the availability of treatment and management. Also screening is very important especially in developing countries as the early treatment is essential for a good visual and learning outcome [1][2][3][4][5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we conclude that the prevalence of secondary surgery in squinted eye patients was low, but With regard to the results of treating amblyopia by occlusion , there were a high number in delaying treating amblyopia which may suggest the distance of the patients' domicile from hospital or lack of education , So we recommend the importance of inform and educate other health care practitioners, including primary care physicians, as well as teachers, parents, and patients about the visual complications of strabismus and the availability of treatment and management. Also screening is very important especially in developing countries as the early treatment is essential for a good visual and learning outcome [1][2][3][4][5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Surgery does not improve the esotropia that occurs without eyeglasses but is performed to correct any residual deviation that remains after treatment with eyeglasses. A randomized, multicenter trial showed a slight improvement in postoperative alignment for patients with esotropia who, before surgery, had fusion after a week of wearing eyeglass-mounted prisms to mimic the effect of surgery (prism adaptation), as compared with patients who had surgery without prism adaptation or who did not have fusion with the prisms (18)(19)(20). However, the benefit, although statistically significant, was modest, and this technique is not universally used.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical technique includes two-, three-or four-muscle surgery done in one or two stages. [5][6][7][8] It is advised by most authors that up to two-muscle surgery should be performed in one stage and if there is any exodeviation remaining, it should be corrected by a second stage surgery. 6 According to Kushner et al, unilateral recession and resection procedure should be performed for primary exotropia.…”
Section: Discussionmentioning
confidence: 99%